One-pot synthesis of 2, 3-disubstituted dihydrobenzofurans and benzofurans via rhodium-catalyzed intramolecular C–H insertion reaction. Issue 31 (20th March 2015) - Ma, Xueji; Wu, Feifei; Yi, Xiaofei; Wang, Hangxiang; Chen, Wanzhi
Abstract : Intramolecular sp 3 C–H insertion of α-imino carbenoid. One pot synthesis of benzofuran derivatives. Abstract : Intramolecular sp 3 C–H insertion reaction of α-imino rhodium carbene generated from N -sulfonyl-1, 2, 3-triazoles has been described. A number of 2, 3-dihydrobenzofuran and benzofuran derivatives have been obtained in good to excellent yields.